2001
DOI: 10.1203/00006450-200103000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Hypocarbia during the First 24 Postnatal Hours and White Matter Echolucencies in Newborns ≤28 Weeks Gestation

Abstract: The purpose of the present study was to test the hypothesis that newborns Յ28 wk gestation who have a Pco 2 measurement in the lowest gestational age-specific quartile (hypocarbia) on the first day of life are not at increased risk for ultrasonographic white matter echolucency (EL) after adjustment for confounders. The sample consisted of 799 infants Յ28 wk gestation born during 1991-1993. Forty-eight infants with EL were classified as cases and compared with 751 controls, i.e. those without EL. We performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…In none of these studies were cohorts larger than 300 infants studied. In the only large cohort study to date, Damman et al (32) found among 799 Ͻ28-wk infants that first-day PaCO 2 values in the lowest quartile were predictive of white matter echolucencies, although multivariate significance was not attained.…”
Section: Discussionmentioning
confidence: 97%
“…In none of these studies were cohorts larger than 300 infants studied. In the only large cohort study to date, Damman et al (32) found among 799 Ͻ28-wk infants that first-day PaCO 2 values in the lowest quartile were predictive of white matter echolucencies, although multivariate significance was not attained.…”
Section: Discussionmentioning
confidence: 97%
“…Vasoconstriction induced by hypocarbia would have a similar effect. Although the effect of hypocarbia on brain damage has been confirmed in clinical studies, such an association has not been shown in the case of hypotension [10,14,16].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Mice deficient in key adhesion molecules are protected from ischemic injury (61,62). Dammann and Leviton (63) have proposed that proinflammatory cytokines might be the link between prenatal intrauterine infection and neonatal brain damage, although there is also strong support of an ischemic component to the pathogenesis of PVL (58,64). We speculate that activated neutrophil-endothelial interactions could be enhanced by both components, linking inflammatory cytokines with hypoperfusion mechanistically in a common pathway toward "vascular failure" in the pathogenesis of PVL.…”
Section: Neutropenia Onset and Neuroprotectionmentioning
confidence: 99%